Gestational age-adapted oxygen saturation targeting and outcome of extremely low gestational age neonates (ELGANs) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: Optimal oxygen saturation (SpO2) targets for extremely low gestational age neonates (ELGANs, gestational age [GA]